Local Discouragement and Global Collapse: A Theory of Coordination Avalanches - Jeitschko, Thomas D; Taylor, Curtis R (American Economic Review, 2001)
We study a dynamic game in which all players initially possess the same information and coordinate on a high level of activity. Eventually, players with a long string of bad experiences become inactive. This prospect can cause a coordination avalanche in which all activity in the population stops. Coordination avalanches are part of Pareto-efficient equilibria; they can occur at any point in the game; their occurrence does not depend on the true state of nature; and allowing players to exchange information may merely hasten their onset. We present applications to search markets, organizational meltdown, and inefficient computer upgrades. (JEL D83)